The diagnostic accuracy of HbA1c, compared to the oral glucose tolerance test, for screening for type 2 diabetes mellitus in Africa—a systematic review and meta-analysis - Chivese, T; Hirst, J; Matizanadzo, JT; Custodio, M; Farmer, A; Norris, S; Levitt, N (Wiley, 2021)
Objective To assess the diagnostic accuracy of glycated haemoglobin A1c (HbA1c), compared to fasting plasma glucose (FPG) and the oral glucose tolerance test (OGTT), in screening for type 2 diabetes (T2D) in Africa.